Comparative Analysis of AES-ECC and AES-ECDH Hybrid Models for a Client-Server System - Sharma, Samiksha; Pokharana, Anchal (2021 2nd Global Conference for Advancement in Technology (GCAT), 2021)
Data security refers to safeguard or protect the data. Data security is an essential prerequisite of the world today because of internet that provides a medium for communication between different communities of the world. Communication can be through a wireless media or wired, that requires security of data while transmitting through it because such mediums are susceptible to different external threats, so there's a strong need of data security for those channels. Cryptography is an art to write code for solving such data threats related problems for communications over an unsecure channel. Cryptography provides diverse set of services to the data such as authentication, privacy, integrity and nonrepudiation through a wide range of techniques. It is broadly classified into two categories named as symmetric and asymmetric cryptography; symmetric technique is fast and uses the same key for encrypting the data and converting the cipher back to its original text using decryption process whereas asymmetric requires different key pair for encrypting and decrypting data. This paper presents a comparative analysis of two hybrid models AES-ECC and AES-ECDH implemented for a client server system. AES is a symmetric technique and is first implemented with ECC for a client server system. After first implementation for further enhancement in the security of data communication between client and server, AES is again implemented with another asymmetric technique ECDH commonly known as a key agreement protocol and a variant of Diffie-Hellman combined with elliptic curve cryptography that adds up more security by establishing a shared secret after a successful key agreement between client and server. After implementing, both the models are analyzed on the basis of various parameters. This paper thus presents the comparison between AES-ECC and AES-ECDH on the basis of various metrics that signify the performance, effectiveness, strength and weakness of an algorithm and also the paper will verify which hybrid technique will be more superior in providing the security and effective delivery of confidential information for a client server communication system.